Ecotheology: A Solution to Improve the Tourism Industry and Help Create a Golden Indonesia by 2045 - Redy Harya Putra; Hardiansyah; Muhammad Fikri Maulana; Basnendar Herry Prilosadoso; Muhammad Halfi Indra Syahputra (Yayasan Inovasi Kemajuan Intelektual, 2025)
Indonesia faces significant challenges in balancing economic growth in the tourism sector with environmental preservation to achieve the vision of Golden Indonesia 2045. This study aims to explore the concept of ecotheology as a fundamental solution to advancing sustainable tourism. Ecotheology offers an approach that integrates spiritual and theological values with ecological responsibility, viewing nature not merely as an economic commodity but as a sacred heritage to be preserved. Using qualitative methods and literature studies, this article analyzes how the internalization of ecotheological values ​​in tourism policy can mitigate the negative impacts of mass tourism and environmental degradation. The results of the study indicate that ecotheology can create an ethnically based tourism model that not only increases the industry's global competitiveness but also ensures the resilience of natural resources for future generations. The implementation of ecotheology in the national tourism strategy is predicted to be an important pillar in realizing a prosperous, independent, and sustainable Golden Indonesia 2045.